PHYCCTM Development Based On KKNI On Impuls And Momentum Material To Increase HOTS And Independent Character - Soeharto Soeharto (STAI Miftahul Ula Nganjuk, 2017)
This study aimed to: (1) Produce KKNI-based PhyCCTM learning tool to improve HOTS and independent character Learners, (2) to know the result of HOTS improvement in Physics learning by using KKNI-based PhyCCTM Learning Tool developed, (3) to know the level of character category self-supporting Learners in Physics learning using KKNI-based PhyCCTM learning tools developed, and (4) to know the effect of applying learning using KKNI-based PhyCCTM learning device to control class and experiment on HOTS and Independent character of Learners. The developed product uses R & D method in the form of KKNI-based PhyCCTM learning device on impulse and momentum materials covering Syllabus, RPP, Teaching Material, LKPD, HOTS Evaluation Test and Self Character Sheet. The study was conducted in SMAN 8 Yogyakarta and SMAN 1 Kasihan. The results showed that (1) PhyCCTM-based learning tools KKNI worthy of the category